Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fimmu.2016.00282
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Affects the Composition of Blood Cell-Derived Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) are specifically loaded with nucleic acids, lipids, and proteins from their parental cell. Therefore, the constitution of EVs reflects the type and status of the originating cell and EVs in melanoma patient’s plasma could be indicative for the tumor. Likewise, EVs might influence tumor progression by regulating immune responses. We performed a broad protein characterization of EVs from plasma of melanoma patients and healthy donors as well as from T cells, B cells, natural killer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 67 publications
3
35
0
Order By: Relevance
“…Recent studies of EVs in patients with cancer indicate that these vesicles are heterogeneous, encompassing a mixture of EVs derived from normal and tumour cells [8,17]. Only some of EVs populating all body fluids in these patients are tumour-derived and it is likely that the ratios of tumour cell-derived vs normal cell-derived EVs vary from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of EVs in patients with cancer indicate that these vesicles are heterogeneous, encompassing a mixture of EVs derived from normal and tumour cells [8,17]. Only some of EVs populating all body fluids in these patients are tumour-derived and it is likely that the ratios of tumour cell-derived vs normal cell-derived EVs vary from patient to patient.…”
Section: Discussionmentioning
confidence: 99%
“…Different sample types were subjected to bead-based multiplex EV analysis by flow cytometry (MACSPlex Exosome Kit, human, Miltenyi Biotec) ( 9 , 10 ), with details regarding sample preparation and normalization summarized in Table S2 in Supplementary Material. Unless indicated otherwise, EV-containing samples were processed as follows: Samples were diluted with MACSPlex buffer (MPB) to, or used undiluted at, a final volume of 120 µL and loaded onto wells of a pre-wet and drained MACSPlex 96-well 0.22 µm filter plate before 15 µL of MACSPlex Exosome Capture Beads (containing 39 different antibody-coated bead subsets) were added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on the impact of melanoma on EV formation, most EVs in the isolates originated from PLTs . Helley et al also demonstrated that the number of EVs originating from PLTs also increased in conjunction with advanced malignant tumour stages in human patients.…”
Section: Discussionmentioning
confidence: 99%